Novel Strategies for Endothelial Preservation in Lung Transplant Ischemia-Reperfusion Injury - Jungraithmayr, Wolfgang (Frontiers in Physiology, 2020)
Lung ischemia reperfusion (IR) injury inevitably occurs during lung transplantation. The pulmonary endothelium is the primary target of IR injury that potentially results in severe pulmonary dysfunction. Over the last decades, various molecules, receptors and signalling pathways were identified in order to develop treatment strategies for the preservation of the pulmonary endothelium against IR injury. We here review the latest and most promising therapeutic strategies for the protection of the endothelium against IR injury. These include the stabilization of the endothelial glycocalyx, the inhibition of endothelial autophagy, the inhibition of adhesion molecules, the targeting of angiotensin-converting enzyme, and traditional viral and novel non-viral gene transfer approaches. Though some of these strategies proved to be promising in experimental studies, very few of these treatment concepts made the transfer into clinical application. This dilemma underscores the need for more experimental evidence for the translation into clinical studies to invent therapeutic concepts against IR injury-mediated endothelial damage.